Hypertension Development by Midlife and the Roles of Premorbid Cognitive Function, Sex, and Their Interaction. Issue 4 (April 2019) - Altschul, Drew M.; Wraw, Christina; Der, Geoff; Gale, Catharine R.; Deary, Ian J.
Abstract : Higher early-life cognitive function is associated with better later-life health outcomes, including hypertension. Associations between higher prior cognitive function and less hypertension persist even when accounting for socioeconomic status, but socioeconomic status-hypertension gradients are more pronounced in women. We predicted that differences in hypertension development between sexes might be associated with cognitive function and its interaction with sex, such that higher early-life cognitive function would be associated with lower hypertension risk more in women than in men. We used accelerated failure time modeling with the National Longitudinal Study of Youth 1979. Cognitive function was assessed in youth, when participants were aged between 14 and 21 years. Of 2572 men and 2679 women who completed all assessments, 977 men and 940 women reported hypertension diagnoses by 2015. Socioeconomic status in youth and adulthood were investigated as covariates, as were components of adult socioeconomic status: education, occupational status, and family income. An SD of higher cognitive function in youth was associated with reduced hypertension risk (acceleration factor: ĉ=0.97; 95% CI, 0.96–0.99; P =0.001). The overall effect was stronger in women (sex×cognitive function: ĉ=0.97; 95% CI, 0.94–0.99; P =0.010); especially, higher functioning women were less at risk than their male counterparts. This interaction was itself attenuated by a sex by family income interaction. People with better cognitive function in youth, especially women, are less likely to develop hypertension later in life. Income differences accounted for these associations. Possible causal explanations are discussed. Abstract : Supplemental Digital Content is available in the text.